Circadian Rhythm Sleep Disorder: Irregular Sleep Wake Rhythm Type - Zee, Phyllis C. (2009)
Irregular Sleep Wake Rhythm Disorder (ISWRD) is characterized by the relative absence of a circadian pattern in an individual’s sleep-wake cycle. Significant changes in circadian regulation occur with aging and with neurodegenerative diseases, such as Alzheimer’s disease prevalent in older adults, which are likely to contribute to the prevalence of ISWRD seen in these populations, although ISWRD is also seen in traumatic brain injury and mental retardation populations. ISWRD is thought to result from some combination of; degeneration or decreased neuronal activity of suprachiasmatic nucleus (SCN) neurons, decreased responsiveness of the circadian clock to entraining agents such as light and activity, and decreased exposure to bright light and structured social and physical activity during the day. Treatment of ISWRD seeks to consolidate sleep during the night and wakefulness during the day; primarily through restoring or enhancing exposure to the various SCN time cues, or “zeitgebers”. Studies of the effectiveness of pharmacologic treatments for ISWRD have generally yielded negative or inconsistent results. In general multi-modal non-pharmacological approaches involving increased exposure to light, increased physical and social activities and improved sleep hygiene have been the most successful therapeutic approaches.